2017
DOI: 10.1002/stem.2729
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Culture Reduces Cell Size By Increasing Vesicle Excretion

Abstract: Our previous study has shown that three-dimensional (3D) culture decreases mesenchymal stem cell (MSC) size, leading to enhanced trafficking ability and reduced lung vascular obstructions. However, the underlying mechanisms are unclear. In this study, we proposed that 3D culture reduces MSC size by increasing vesicle excretion. Scanning electron microscope showed that 3D culture markedly increased the amount of membrane-bound vesicles on the cell surface. In consistence, tunable resistive pulse sensing quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…After 3D spheroids culture, the diameter of MSCs significantly decreased (Fig. 1 A–D), which is consistent with our previous studies [ 11 , 14 , 27 ]. Importantly, annexin V/PI staining of the cells by flow cytometry analysis showed that the 3D spheroid culture did not increase cell apoptosis (Fig.…”
Section: Resultssupporting
confidence: 92%
“…After 3D spheroids culture, the diameter of MSCs significantly decreased (Fig. 1 A–D), which is consistent with our previous studies [ 11 , 14 , 27 ]. Importantly, annexin V/PI staining of the cells by flow cytometry analysis showed that the 3D spheroid culture did not increase cell apoptosis (Fig.…”
Section: Resultssupporting
confidence: 92%
“…50 Also, 3D cultures show an increase in vesicle secretion, which could potentially contain STC1. 46 These results are in line with ours and hinted at a mechanosensitive regulation of STC1. Here, we have shown that STC1 is indeed regulated through mechanotransduction pathways, specifically through zyxin and actin-myosin.…”
Section: Discussionsupporting
confidence: 91%
“…Others have reported that depolymerization of actin results in increased vesicle secretion, hinting at a potential mechanism of the increased STC1 secretion. 46 The number of zyxin positive focal adhesions was also reduced in the hypotonic and nutrient deprivation conditions, but not the hypertonic condition, correlating with the STC1 secretion. When zyxin was knocked down, we also found an increase in STC1 secretion, proving a causal link between the two.…”
Section: Discussionmentioning
confidence: 92%
“…Wang et al demonstrated that with the successive adherent cultures of MSCs, the expression level of integrins increased, which was associated with higher levels of phospho-focal adhesion kinase (FAK) and increased attachment to endothelial cells [ 73 ]. Interestingly, MSCs cultured as 3D spheroids are characterized by a significantly smaller size and did not cause detectable infarct in the brain, as demonstrated by Ge et al [ 71 ], and the most plausible reason is that a short period of 3D spheroid culture of MSCs was enough to reduce the size of these cells [ 74 ] as well as the expression levels of many integrins [ 73 ]. Our analysis of the literature shows that MSCs at passages 3 and 4 were most frequently used in clinical trials.…”
Section: Resultsmentioning
confidence: 99%